2021
DOI: 10.3390/cancers13143604
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB3 Inhibition Sensitizes DNA Crosslinking Chemotherapies by Suppressing Fanconi Anemia Repair

Abstract: Replicative repair of interstrand crosslinks (ICL) generated by platinum chemotherapeutics is orchestrated by the Fanconi anemia (FA) repair pathway to ensure resolution of stalled replication forks and the maintenance of genomic integrity. Here, we identify novel regulation of FA repair by the cancer-associated glycolytic enzyme PFKFB3 that has functional consequences for replication-associated ICL repair and cancer cell survival. Inhibition of PFKFB3 displays a cancer-specific synergy with platinum compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…4A, B). Considering that elevated DNA oxidation can result from reduced DNA repair capacity and that PFKFB3 can directly affect DNA repair (9,30), we hypothesized that PFKFB3 is involved in the DNA damage response or repair in lung cancer cells insulted by ROS. Under standard conditions, oxidized nucleotides can be directly removed from DNA via the base-excision repair (BER) mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4A, B). Considering that elevated DNA oxidation can result from reduced DNA repair capacity and that PFKFB3 can directly affect DNA repair (9,30), we hypothesized that PFKFB3 is involved in the DNA damage response or repair in lung cancer cells insulted by ROS. Under standard conditions, oxidized nucleotides can be directly removed from DNA via the base-excision repair (BER) mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings indicate that oxidative stress driven by PFKFB3 inhibition in TKI-treated cells promotes DNA oxidation, resulting in double-strand DNA damage. While the role of PFKFB3 in regulating DNA integrity through homologous recombination (30)and miss-match repair pathways is known (30) (9), we discovered that PFKFB3 also regulates base excision repair in TKI-treated cells. Specifically, we found that PFFKB3 sustains the expression of DNA-glycosylases such as MPG, NTHL1, and UNG1/2, which recognize and eliminate modified nucleotides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, therapies targeting an enhanced glycolytic caused IVD acidic environment are a new direction worthy to be exploited. KAN, an emerging selective inhibitor of key rate-limiting metabolic kinase PFKFB3, has been used to treat colorectal cancer and elevate the efficacy of interstrand crosslink- (ICL-) inducing cancer therapies due to the function during DNA damage [ 32 , 33 ]. However, research on the diseases principally influenced by its glycolysis regulation function is still blank.…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous targets derived from either upstream or downstream of DDR/FA signaling are under testing to increase the sensitivity of chemotherapy [ 2 , 102 , 103 , 104 ]. Many of them may be promising initially; but nearly all would eventually develop resistance.…”
Section: Prospectivementioning
confidence: 99%